The Role of AEBP1 in Sex-Specific Diet-Induced Obesity - Zhang, Lei (2005)
Obesity is an important risk factor for heart disease, diabetes, and certain cancers, but the molecular basis for obesity is poorly understood. The transcriptional repressor AEBP₁, which functions as a negative regulator of PTEN through a protein-protein interaction, is highly expressed in the stromal compartment of adipose tissues, including proliferative preadipocytes, and its expression is abolished in terminally differentiated, nonproliferative adipocytes. Here we show that transgenic overexpression of AEBP₁ during adipogenesis coupled with a high-fat diet (HFD) resulted in massive obesity in female transgenic (AEBP₁ᵀᴳ) mice via adipocyte hyperplasia. AEBP₁ levels dynamically changed with aging, and HFD induced AEBP₁ expression in females. Thus, HFD-fed AEBP₁ᵀᴳ females display hyperinduction of AEBP₁ and a marked reduction of PTEN level with concomitant hyperactivation of the survival signal in white adipose tissue. Our results suggest that AEBP₁ plays a key functional role in in vivo modulation of adiposity via fat-cell proliferation and is involved in a sex-specific susceptibility to diet-induced obesity by the estrogen signaling pathway.